Numerical Investigation on Flexural Beams Made with Metakaolin and Shredded Plastic Waste - Sivaraj, M.; R. Sundararajan, Dr.; Vivek, K.; T. Senthil Vadivel, Dr. (International Journal of Engineering and Technology, 2018)
Among various building materials, concrete is the most widely used conventional material. Nowadays many scientists are on a hunt for a substitute material for constructionthat is eco-friendly and made from industrial waste products and offer sustainable development. In this study, cement was partially substituted by metakaolin of varying percentage as 0%, 2.5%, 5%, 7.5% and 10% by weight of cement. Shredded plastic waste of 0.5% by weight was added to concrete by replacing coarse aggregate in the concrete. M20 grade concrete is used for beams. Optimum replacement percentage of metakaolin was determined from the tests. Ultimate load carrying capacity of beams produced with the optimum replacement percentage was compared with the numerical investigation done by finite element modelling package ANSYS 12.0.Â